Strengthening State Defense Based on Islamic Values: Evidence from the Students at State Islamic Institute - In'ami, Moh; Suryadi, Bambang (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
Although state defense activities have been introduced for quite a long time in Islamic universities, students' understanding of defending a country that is free from values and based on Islamic values is still a matter of debate. This study analyzes the Islamic values in the state defense strengthening program at the Mahadipa Student Regiment Unit 954 Yudhagama. This type of research is field research with a qualitative-phenomenological approach. Data collection uses documentation, observation, and interviews. The study's respondents were five students representing the members of the Mahadipa Student Regiment Unit 954 Yudhagama in Kudus Central Java. The results of this study indicate that the Islamic values introduced in the strengthening state defense program for members of the Mahadipa Student Regiment Unit 954 Yudhagama are manifested in life training full of discipline and a healthy lifestyle. Among these Islamic values are living resiliently, solidarity, togetherness, honesty, a knightly spirit, and preparing oneself to defend the country. Islamic values can be seen in daily life activities, both in vertical and horizontal relationships, that describe the characteristics of a holistic Muslim.